2022
DOI: 10.3390/ijms23126721
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Identified Key Pathways and Genes Regulating Differentiated Stigma Color in Melon (Cucumis melo L.)

Abstract: Stigma color is an important morphological trait in many flowering plants. Visual observations in different field experiments have shown that a green stigma in melons is more attractive to natural pollinators than a yellow one. In the current study, we evaluated the characterization of two contrasted melon lines (MR-1 with a green stigma and M4-7 with a yellow stigma). Endogenous quantification showed that the chlorophyll and carotenoid content in the MR-1 stigmas was higher compared to the M4-7 stigmas. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The green color of stigmas is likely caused by accumulation of chlorophyll, the same pigment that gives plants leaves and fruits their characteristic green appearance. The genetic study for melon ( Cucumis melo ) stigma color showed that green stigma is dominant over the yellow one; transcriptomic analysis proposed that the yellow color is probably due to the break-down of chloroplast structure interfering with chlorophyll biosynthesis; in contrast, the green stigmas are a functional accumulation of chlorophyll ( Lv et al., 2022a ; Lv et al., 2022b ). This might also be true for the green/yellow stigma of bitter gourd.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The green color of stigmas is likely caused by accumulation of chlorophyll, the same pigment that gives plants leaves and fruits their characteristic green appearance. The genetic study for melon ( Cucumis melo ) stigma color showed that green stigma is dominant over the yellow one; transcriptomic analysis proposed that the yellow color is probably due to the break-down of chloroplast structure interfering with chlorophyll biosynthesis; in contrast, the green stigmas are a functional accumulation of chlorophyll ( Lv et al., 2022a ; Lv et al., 2022b ). This might also be true for the green/yellow stigma of bitter gourd.…”
Section: Discussionmentioning
confidence: 99%
“…In a rice indica cultivar, its purple apiculi and stigma were genetic regulated by the interaction of two genes involved the anthocyanin biosynthesis pathway: OsC1 (encoding a R2R3-MYB transcription factor) and OsDFR (encoding a dihyroflavonol 4-reductase) ( Meng et al., 2021 ). Recent two transcriptomic studies aimed at revealing the gene network were conducted and showed that the yellow stigma in tomato is very likely due to the accumulation of yellow-colored flavonoid naringenin chalcone, whereas the melon yellow stigma is due to break-down of chloroplast structure interfering chlorophyll biosynthesis ( Zhang et al., 2017 ; Lv et al., 2022a ). Despite the crucial functional roles of stigmas play in plant reproduction, there has not been sufficient researches dedicated to the color of stigma.…”
Section: Introductionmentioning
confidence: 99%
“…All the gene primer information can be seen in Supplementary Table S2. qRT-PCR analysis was performed by following three biological replicates per sample, as reported earlier [54]. The relative expression levels of putative identified CmGGP1 and associated genes were determined using an earlier reported method [55], respectively.…”
Section: Endogenous Determination Of Asa Content and Gene Expression ...mentioning
confidence: 99%
“…Data from the transmission electron microscopy of chloroplast structures, RNA sequencing and transcriptome analysis, and qRT-PCR analysis, altogether concluded that relative expression of five key genes (CAO, CHLH, CRD, HEMA, POR) of chlorophyll biosynthesis pathway were observed to be highly expressed in green stigma melon than the yellow one. 16 The future breeding programmes aiming to increase the extent of natural pollination in melon by the insects could target the expression of these key genes. In addition, the recently identified QTLs linked to stigma color namely, SC2.1 and SC8.1 would further help in marker-assisted selection of a particular type of melon stigma color cultivars.…”
Section: Genomics Of Melon Plant Physiologymentioning
confidence: 99%
“…(a) Extraction of the total RNA of an individual plant, (b) cDNA libraries construction and resequencing, (c) Quantitative Reverse Transcription PCR (qRT-PCR) using the primers designed for candidate genes based on the known genome sequence, (d) Identification and annotation of differentially expressed genes. [13][14][15][16][17] Altogether, these molecular studies would provide valuable genetic resources that can be directly used in molecular breeding for melon crop improvement.…”
Section: Introductionmentioning
confidence: 99%